From Hierarchy To Reciprocity: Re-Envisioning Teacher-Student Relations In Islamic Education Through Qira’ah Mubadalah - Mahmud Yunus Mustofa; Muh Syauqi Malik; Mikke Novia Indriani; Makmur Sofyan Mustofa (Istifkar: Media Transformasi Pendidikan, 2026)
Teacher-student relationships within the Islamic educational tradition are frequently characterized by a unidirectional, vertical hierarchy in which the student is relegated to a passive recipient of knowledge. This power imbalance often triggers pedagogical stagnation and, in extreme cases, manifests as physical violence or emotional detachment. This study proposes a paradigm shift by re-envisioning the dynamics of teacher-student relations through the lens of Mubādalah (Reciprocity). Employing a qualitative approach grounded in hermeneutic analysis, this paper deconstructs the conventional "subject-object" dichotomy and replaces it with a "subject-to-subject" partnership grounded in Mubādalah principles. The analysis applies a three-step Mubādalah framework: first, identifying universal Islamic principles of justice; second, extracting core pedagogical values from religious texts; and third, reciprocally distributing these values to both teachers and students. The findings demonstrate that applying Mubādalah to teacher-student relations transforms the classroom into a space of mutual dignity, where both parties become active participants in a shared spiritual and intellectual journey. This reciprocal model does not diminish the teacher's role but reframes their position from an absolute authority to a mentor and facilitator grounded in compassion (raḥmah). Ultimately, this research contributes to the discourse on Islamic educational reform by providing a theological and methodological foundation for creating non-violent, egalitarian, and harmonious learning environments suited to the challenges of the 21st century.